2016
DOI: 10.5415/apallergy.2016.6.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Family quality of life among families of children with atopic dermatitis

Abstract: BackgroundAtopic dermatitis (AD) may cause emotional distress and impairs the quality of life (QoL) in children and their families.ObjectiveWe examined family QoL of children with AD and explored associated factors such as disease severity and psychosocial factors among parents of children with AD.MethodsStudy participants were 78 children (1 month to 16 years old) diagnosed with AD and their parents visiting an outpatient clinic of the Department of Pediatrics in Inha University Hospital. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
4
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 28 publications
2
35
4
8
Order By: Relevance
“…The impact of AD on family QoL was specifically investigated in a questionnaire‐based study of South Korean families of children with AD and showed that in families of children with more severe AD the probability of a low family QoL was 6.6‐times more than in families of children with less severe disease . Families of girls with AD also had lower QoL than families of boys with AD, which may be indicative of sex differences in perception by both the child and the parents . Thus, the QoL burden of AD extends beyond individuals affected by the disease.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The impact of AD on family QoL was specifically investigated in a questionnaire‐based study of South Korean families of children with AD and showed that in families of children with more severe AD the probability of a low family QoL was 6.6‐times more than in families of children with less severe disease . Families of girls with AD also had lower QoL than families of boys with AD, which may be indicative of sex differences in perception by both the child and the parents . Thus, the QoL burden of AD extends beyond individuals affected by the disease.…”
Section: Quality Of Lifementioning
confidence: 99%
“…9,31 While this association is obvious and expected, our findings offer longitudinal evidence that children's higher levels of quality of life and its improvement strongly affect the dynamics of AD-related quality of life in the family. Greater improvement in children's quality of life was also associated with greater improvement in parental quality of life.…”
Section: Discussionmentioning
confidence: 60%
“…5,6 Apart from difficulties with child's scratching, skin rubbing and overall irritation, sleep disruption is a cardinal feature in childhood AD. 9 Moreover, because asthma and allergic rhinitis are frequent concurrent chronic conditions with AD, comorbidities in children with AD put additional strain on the parents. 1,8 Evidence suggests that the level of family life quality directly results from AD severity in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jang et al [12] report on the quality of life of the family having children with atopic dermatitis. Chronic urticaria also affects the quality of life.…”
mentioning
confidence: 99%